(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In recent times, there has been a major concern about how effectively agricultural products are marketed in India. High and volatile consumer prices are said to be driven by insufficient infrastructure for marketing and weak channel connections. The wheels that move economic operations are marketing infrastructure. In India, a major portion of the population relies on agriculture for their living, either directly or indirectly benefiting the general rural population as a whole. 77% of people who are employed in the North-Eastern region of India work in agriculture. The evolution of the marketing mechanism for agriculture is crucial. Because the Market Regulation Act has not been properly implemented. Private merchants dominate the marketing of agricultural goods in the North Eastern States. Although the North Eastern States produce a large number of fruits, spices, and other products, they earlier were unable to match pricing with the marketplaces in other states. Additionally, the infrastructure, procurement procedures, marketing strategies, and processing facilities all provide serious challenges to rural marketing in the North-East (NE) area. The underdevelopment of agro-industries in the area to better add value to horticulture products is also significantly attributed to social and cultural norms. To enhance the marketing environment and the farmer’s economic advantages through better management of various post-harvest functions of the agricultural products, it is crucial to identify the issues in the NE area. This paper examined the current state of agricultural marketing in NER and attempt to discuss its challenges and future opportunities. Additionally, it proposes some recommendations for future improvements in agricultural marketing.